Derivatives of Inner Functions - Mashreghi, Javad; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Derivatives of Inner Functions was inspired by a conference held at the Fields Institute in 2011 entitled "Blaschke Products and Their Applications." Inner functions form an important subclass of bounded analytic functions. Since they have unimodular boundary values, they appear in many extremal problems of complex analysis. They have been extensively studied since the early twentieth century and the literature on this topic is vast. This book is devoted to a concise study of derivatives of inner functions and is confined to treating the integral means of derivatives and presenting a comprehensive list of results on Hardy and Bergman means. This self-contained monograph allows researchers to get acquainted with the essentials of inner functions, rendering this theory accessible to graduate students while providing the reader with rapid access to the frontiers of research in this field.
Keywords: Mathematics; Functional analysis; Functions of complex variables; Differential equations, partial; Mathematics; Functions of a Complex Variable; Functional Analysis; Several Complex Variables and Analytic Spaces